1997
DOI: 10.1103/physrevc.56.2747
|View full text |Cite
|
Sign up to set email alerts
|

Exact baryon, strangeness, and charge conservation in hadronic gas models

Abstract: Relativistic heavy ion collisions are studied assuming that particles can be described by a hadron gas in thermal and chemical equilibrium. The exact conservation of baryon number, strangeness and charge are explicitly taken into account. For heavy ions the effect arising from the neutron surplus becomes important and leads to a substantial increase in e.g. the π − /π + ratio. A method is developed which is very well suited for the study of small systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 18 publications
2
42
0
1
Order By: Relevance
“…[5]. More recently, it has been pointed out [6,7] that in the canonical ensemble (CE) with exact conservation of charges, scaled second moment (scaled variance) of the multiplicity distribution of any particle does not converge to the corresponding GC value even in the thermodynamic limit, unlike the mean [8,9]. This was fairly understood among experts in statistical mechanics [10], but probably it has been shown explicitely for the canonical relativistic gas for the first time in refs.…”
Section: Introductionmentioning
confidence: 99%
“…[5]. More recently, it has been pointed out [6,7] that in the canonical ensemble (CE) with exact conservation of charges, scaled second moment (scaled variance) of the multiplicity distribution of any particle does not converge to the corresponding GC value even in the thermodynamic limit, unlike the mean [8,9]. This was fairly understood among experts in statistical mechanics [10], but probably it has been shown explicitely for the canonical relativistic gas for the first time in refs.…”
Section: Introductionmentioning
confidence: 99%
“…Strangeness enhancement in Au-Au system does not definitely look like being of canonical origin, whereas Si-Au and Si-Al follow roughly the curve at the normal nuclear density Whereas the kaon enhancement with increasing centrality seems not to be compatible with a purely canonical effect, inelastic pp and central p-A and A-A systems considered in ref. [8] show a different behaviour with increasing volume. Therein, it was found that K/π ratios clearly follow the canonical curves.…”
Section: Numerical Resultsmentioning
confidence: 98%
“…The integral can be turned into a sum over many indices of modified Bessel functions I n (x), yet its evaluation is very time consuming and becomes impractical with baryon number larger than ∼ 10 [8]. Therefore, we have chosen another approach, which has been applied in elementary collisions [7,17].…”
Section: The Analytical Developmentmentioning
confidence: 99%
See 2 more Smart Citations